Transformasi Usaha Minuman Mr Brew Indonesia Kedalam New Retail Concept - Entis Sutisna, Rizki (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2022)
The impact of the covid-19 pandemic has changed the state or habits, be it in the field of education, social, even economic. So pandemics do not allow a person to meet in person with others or face-to-face. The purpose of this study is to find out business actors in developing the creative economy in the the coffe beverage sector during the covid-19 pandemic. The research data was obtained through the interview process with the owner of the coffe shop â€œMR Brew Indonesiaâ€ located in Bandung. The result of this research aim ti find out business actors in the development of the creative economy in the coffe beverage sector during the covid-19 pandemic such as sales channel and digital marketing.